ITF Centenary Congress 1896-1996 : exhibition-concept - Steenhaut, Wouter; Vermote, Michel; Gobyn, Ronny (Ghent: Amsab-ISG, 1994)
"presented by Amsab Ghent Congres gehouden van 30 juni tot 2 juli 1996"